PTEN Regulates Renal Extracellular Matrix Deposit via Increased CTGF in Diabetes Mellitus. Issue 5 (18th October 2015) - Zhu, Lin; Zhao, Song; Liu, Shuxia; Liu, Qingjuan; Li, Fan; Hao, Jun
ABSTRACT: Extracellular matrix accumulation and fibrosis are the features of diabetic nephropathy. PI3K (phosphatidylinositol 3‐kinase)/Akt (protein kinase B) signal pathway and its inhibitor PTEN (phosphatase and tensin homolog deleted on chromosome 10) are revealed to modulate renal fibrosis. However, the exact mechanism is still not well known. In the present study we found that compared with normal mice, diabetic mice showed decreased PTEN, increased phospho‐Akt (Ser 473), phospho‐Akt (Thr 308), CTGF (connective tissue growth factor), α‐SMA (α‐smooth muscle actin), and matricellular protein in kidney. Knocking down of PTEN caused an increase in phospho‐Akt (Ser 473), phospho‐Akt (Thr 308), CTGF, secreted fibronectin, and secreted Col 3 in HKC cells (human renal tubular epithelial cells). Again, in vitro experiment revealed 1.89, 2.18, 1.92, 3.06, 2.06‐fold increases of phospho‐Akt (Ser 473), phospho‐Akt (Thr 308), CTGF, secreted fibronectin, and secreted Col 3 in high glucose‐stimulated HKC cells in comparison with normal control cells. Furthermore, knocking down of CTGF reversed increased secreted fibronectin and Col 3 in high glucose‐treated HKC cells. Moreover, transfection of PTEN expression vector prevented high glucose‐caused these changes in HKC cells. Especially, CTGF expression, secretion of fibronectin and Col 3 were, respectively, decreased by 38.81, 53.85, and 39.12%. The treatment of LY294002 inhibited phospho‐Akt (Ser 473) and phospho‐Akt (Thr 308) expression followed by decreased CTGF, secretory fibronectin and secretory Col 3 in high glucose‐treated HKC cells. In the end our study suggests that PTEN regulates renal extracellular matrix production via activated Akt and increased CTGF in diabetes mellitus. J. Cell. Biochem. 117: 1187–1198, 2016. © 2015 Wiley Periodicals, Inc.